How have thermal conditions changed in different phenological stages of apple (Malus domestica) in Northeastern Hungary? - Somfalvi-Tóth, Katalin; Hoffmann, Richárd; Percze, Gabriella; Jócsák, Ildikó (Acta Agraria Debreceniensis, 2023)
In temperate climates, most fruit trees need cold weather, low temperatures in winter, and a certain amount of heat during the growing season until harvest. One of the most apparent effects of climate change is the elevated temperature in all seasons of the year. In our study, the changes in thermal conditions have been calculated in Hungary’s most significant growing region of apples using the Chill Unit for winters and the Growing Degree Days for summers. The meteorological data were obtained from the gridded dataset of the Hungarian Meteorological Service on a 10 km × 10 km grid, so the whole studied area is well-covered over the last 50 years. The results show that the trees are more exposed to early budding than a few decades ago. Furthermore, the accumulated heat amount in summers has increased drastically, which may increase the heat stress and lead to higher yield losses.